2021
DOI: 10.1530/rep-20-0523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of COVID-19 on male reproduction

Abstract: Invasion or damage of the male reproductive system is one of the reported outcomes of viral infection. Current studies have documented that SARS-CoV-2, which causes COVID-19, can damage the male reproductive system in large part by inflammatory damage caused by cytokine storm. However, whether SARS-CoV-2 can infect the human testis directly and enter semen is controversial. Other adverse effects of SARS-CoV-2 on male reproduction are also of concern and require comprehensive evaluation. Here, we analyze the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 18 publications
0
49
0
5
Order By: Relevance
“…Altered levels of gonadotropins and testosterone in male COVID-19 subjects might be due to the dysregulation of hypothalamic–pituitary–testicular (HPT) axis (Tian and Zhou 2021 ). Nevertheless, SARS-CoV-2-mediated dysregulation of the HPT axis remains unclear (Pal and Banerjee 2020 ).…”
Section: Sars-cov-2 Effects On the Male Reproductive System: Pathologic Alterations And Underlying Mechanismsmentioning
confidence: 99%
“…Altered levels of gonadotropins and testosterone in male COVID-19 subjects might be due to the dysregulation of hypothalamic–pituitary–testicular (HPT) axis (Tian and Zhou 2021 ). Nevertheless, SARS-CoV-2-mediated dysregulation of the HPT axis remains unclear (Pal and Banerjee 2020 ).…”
Section: Sars-cov-2 Effects On the Male Reproductive System: Pathologic Alterations And Underlying Mechanismsmentioning
confidence: 99%
“…As angiotensin-converting enzyme 2 receptors (ACSE2) expression is rich in testes, SARS-CoV-2 may bind these receptors to penetrate cells and initiate its intracellular replication and action (cytotoxicity) that disrupting the testicular hemostasis. Similarly, several studies reported that ACSE2 receptor expression is rich in human male gonads (spermatogonia, Leydig, Sertoli cells, and seminiferous ducts), thus SARS-CoV-2 can bind ACSE2 receptor to disrupt gonadal hemostasis and increase the risk of testicular dysfunction [19][20][21][22]. SARS-CoV-2 may cause spermatogenic failure [20].…”
Section: Possible Mechanisms Of How the Sars-cov-2 Can Infect The Testesmentioning
confidence: 99%
“…Therefore, infection with SARS-CoV-2 can result in wide range of clinical signs. The patients may demonstrate one or more of the following symptoms: respiratory manifestations (Zheng et al 2020 ), gastro-intestinal symptoms and hepatic abnormalities (Zarifian et al 2020 ), integumentary system and skin lesions (e.g., pityriasis rosea, exanthem, papules, vesicles, and urticaria) (Rodriguez-Cerdeira et al 2021 ; Deshmukh et al 2020 ), multisystem inflammatory syndrome and Kawasaki-like syndrome in children (Esmaeilzadeh et al 2021 ; Haslak et al 2020 ), nervous signs (Soltani et al 2021 ; Ellul et al 2020 ), severe immune response (storm of cytokines) (Hu et al 2021 ), and cardiovascular manifestations (Israel et al 2021 ) and may even infect the male reproductive system leading to testicular damage and reduction of male fertility (Roychoudhury et al n.d. ; Tian and Zhou 2021 ).…”
Section: Factors Determining Covid-19 Susceptibility In the Populationmentioning
confidence: 99%